22 Ideas to Fix the World : Conversations with the World's Foremost Thinkers - Sakwa, Richard; Dutkiewicz, Piotr (Book collections on Project MUSE., 2013)
The aftershocks of the 2008 financial crisis still reverberate throughout the globe. Markets are down, unemployment is up, and nations from Greece to Ireland find their very infrastructure on the brink of collapse. There is also a crisis in the management of global affairs, with the institutions of global governance challenged as never before, accompanied by conflicts ranging from Syria, to Iran, to Mali. Domestically, the bases for democratic legitimacy, social sustainability, and environmental adaptability are also changing. In this unique volume from the World Public Forum Dialogue of Civi.